2012
DOI: 10.1007/s00127-012-0473-1
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of eating disorders not otherwise specified in northwestern Spain: population-based study

Abstract: The incidence and prevalence of EDNOS are the highest in the ED cases; furthermore, new cases of ED are observed above the age of 45, which are remarkable data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 32 publications
0
11
0
4
Order By: Relevance
“…An Austrian study assessing the prevalence of eating disorders among 715 women aged 40-60 years found three (0.4%) women presenting symptoms of anorexia nervosa without amenorrhea [ 6 ]. Another European population-based study reported a 0.17% lifetime risk of AN in woman above 45 years [ 5 ]. An American study assessing weight and eating disorders symptoms in 1849 women aged 50 and above, found that 1.6% of them were underweight (<18.5 kg/m2) [ 7 ].…”
Section: Epidemiologymentioning
confidence: 96%
See 2 more Smart Citations
“…An Austrian study assessing the prevalence of eating disorders among 715 women aged 40-60 years found three (0.4%) women presenting symptoms of anorexia nervosa without amenorrhea [ 6 ]. Another European population-based study reported a 0.17% lifetime risk of AN in woman above 45 years [ 5 ]. An American study assessing weight and eating disorders symptoms in 1849 women aged 50 and above, found that 1.6% of them were underweight (<18.5 kg/m2) [ 7 ].…”
Section: Epidemiologymentioning
confidence: 96%
“…It has not been established whether presentations of AN in middle aged and older women represent a continuation of a lifelong illness or late age onset of the disease. In a Spanish population-based study new cases of eating disorders including AN above the age of 45 were observed [15]. However, the data collected from one of the largest national referral centres in the UK suggests that AN in patients above 50 years is a chronic and enduring mental illness with the age of onset being under 25 years [16].…”
Section: Epidemiologymentioning
confidence: 97%
See 1 more Smart Citation
“…13 Thirteen (24.5%) studies reported interviewing participants using [clinical] interviews based on DSM-IV criteria, without specifying details. The remaining 3 studies reported sample sizes ranging from between 30 000 to over 250,000 participants, the 2 two largest using either self-report (N 5 252,838), 77 or interview (N 5 100,000) 59 to assess ED prevalence. Eight of these 10 studies were American.…”
Section: Data Collectionmentioning
confidence: 99%
“…Since the advent of the Diagnostic and Statistical Manual of Mental Disorders, fifth edition (known as DSM-5) and broadening of the diagnostic criteria for anorexia nervosa, investigators have seen a substantial increase in the prevalence of anorexia nervosa 6,7 . Although the disease most commonly affects young women, a population-based study in Europe reported a 0.17% lifetime prevalence of anorexia nervosa in women >45 years of age 8 . Anorexia nervosa might also affect adolescent boys and men, although disease prevalence was 8.1 times higher in women than in men in a population-based study in the USA 9 .…”
Section: Introductionmentioning
confidence: 99%